Research on nonlinear dynamic characteristics of GMA under time delayed feedback control - XU Chenyu; LI Hongzhu; ZHOU Yafu (Jixie chuandong)
ObjectiveTo effectively control the nonlinear characteristics of giant magnetostrictive actuators (GMAs), a combined linear and nonlinear time delayed feedback controller was designed to suppress the main resonance bifurcation and chaotic motion of the GMA system.MethodsBased on the multi-scale method, the analytical solution of the system and the main resonance response equation were solved. Through the numerical simulation, the key structural parameters of the uncontrolled system and the time delayed feedback parameters of the control system were studied to investigate the characteristics of the main resonance and the chaotic motion.ResultsThe research results indicate that uncontrolled systems exhibit bifurcation and multivalued solutions. Appropriately increasing the time delayed gain coefficient can effectively eliminate the main resonance bifurcation and jumping phenomenon, and reduce the chaotic motion region. The results have a certain guiding role in improving the output stability of the GMA systems.